Desenvolvimento e validação de metodologia analítica para determinação de cloridrato de tirofibana e impurezas de síntese e estudo preliminar da estabilidade - Feijó, Adriane Lettnin Roll (2018)
Tirofiban is a non-peptidic inhibitor drug derived from tyrosine that inhibits platelet aggregation at the end of the coagulation cascade, specifically as a glycoprotein (GP) IIb / IIIa receptor antagonist, the most widely used GP inhibitor being the worldwide its new dosage by the FDA in 2013, under the trade name of Agrastat®. ANVISA and international guides determine that marketed medicines must guarantee product quality and consumer safety. In this context, it is essential to develop and validate methods that allow evaluation from the raw material to the pharmaceutical form, contemplating the study of drug stability in the formulations, the analysis of degradation products, identification and determination of the levels of impurities and standardization of production procedures. There are few reports in the literature on the quantitative determination of tirofiban and on degradation under forced conditions. In addition, the literature does not show a record of development and validation of method indicative of stability, determination of impurities of synthesis and products of degradation. This study aimed the development and validation of an indicative method of stability for determination of tirofiban in the presence of two impurities (impurity A and impurity C), as well as to perform a preliminary stability study and to determine the kinetics of degradation related to the main factors of degradation. The method development and validation were carried out in agreement with the main official guides. High-performance liquid chromatography (HPLC) coupled to a photodiode array detector (DAD) at 226 nm using a C18 column (4.6 x 250 mm, 5μm) was used at room temperature with a mobile phase eluted in a gradient mode, consisting of a mixture of 0.1% triethylamine acidified to pH 5.5 with phosphoric acid and acetonitrile, in a flow rate of 1 mL.min-1 and an injection volume of 20 μL. The method presented satisfactory linearity, precision, accuracy and robustness, as well as low limits of detection and quantification, which demonstrate sensitivity in the determination of tirofiban and impurities A and C. It was selective for the determination of the drug and impurities analyzed, without interference of the degradation products generated under forced conditions, data demonstrating the capacity indicative of the stability of the proposed method. Tirofiban was practically stable under oxidative (30% H2O2 for 24 hours) and thermal (75oC for 24 hours) conditions, presenting degradation against UVA light and acid hydrolysis, following the first order kinetics. The results obtained in this work demonstrate the importance of expanding the studies in this area, in order to guarantee the quality of commercialized pharmaceutical products.